PHARMACOECONOMIC EVALUATION FOR DENGUE VACCINE PRICING FOR MALAYSIA: TOWARDS AFFORDABILITY, COST EFFECTIVENESS AND SUSTAINABILITY - Koh, Hock Lye; Teh, Su Yean; Noordin, Noorliza M.; Sulaiman, Lokman H. (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Malaysian health ministry is currently evaluating the licensing of dengue vaccine Dengvaxia using a set of criteria including safety, efficacy and cost-effectiveness. The purpose of this research is to formulate a model framework to assist transparent decision-making. Methods: To quantify the cost-effective price of vaccine, pharmacoeconomic evaluation models are commonly used. We review in this paper dengue economic burdens and pharmacoeconomic models, with particular reference to cost-effectiveness. Results: A major weakness in current pharmacoeconomic models is the omission of cost of vaccine production, which is two orders of magnitude lower than the market price. This paper proposes an inclusive model that yields a highly cost-effective threshold price of dengue vaccine at USD 5 per dose for Malaysia. Conclusion: At USD 5 per dose, Dengue vaccine will be fair, Affordable and sustainable.